Semen and physical examination of bulls - McNitt, J.I.; Kamwanja, L. (1976)
Describes the bull evaluation programme in Malawi. Results of physical and seminal examination of 211 bulls are reported. Semen characteristics of Malawi Zebu and Angoni bulls compared.